Influence of the timing of bronchoscopic alveolar lavage on children with adenovirus pneumonia: a comparative study - Xue-hua Xu (BMC, 2021)
Abstract Background Adenovirus pneumonia is prone to severe clinical and imaging manifestations in children. Bronchoscopic alveolar lavage (BAL) is an important adjunctive therapy for patients with severe imaging findings. The study aimed to evaluate the effect of the timing on the efficacy of bronchoalveolar lavage in children with adenovirus pneumonia. Methods This study included 134 patients with adenovirus pneumonia treated with BAL at Guangzhou Women and Children's Medical Center from January 2019 to January 2020.They were classified into the severe and mild groups. Based on the timing of BAL, each group was divided into the early BAL layer (received BAL within 1–9 days of the illness course) and the late BAL layer (received BAL within 10–14 days of the illness course). The clinical data of patients with different BAL timings were analyzed in two groups. Results Among the 134 patients, 70 were categorized into the mild group and 64 were categorized into the severe group. Of the 134 patients, 42 patients received BAL early (mild group: n = 21 and severe group: n = 21) and 92 patients received BAL later (mild group: n = 49 and severe group: n = 43). In the mild group, the fever and hospital duration were shorter in patients who received BAL early than in those who received BAL later (p < 0.05). However, in the severe group, there were no statistically significant differences in the fever and hospital duration between patients who received BAL early and those who received BAL later. However, the need for mechanical ventilation and the incidence of BAL complications, such as new need for oxygen, were higher in patients who received BAL early than in those who received BAL later in the severe group (p < 0.05). Conclusion For mild adenovirus pneumonia, early BAL may shorten the fever and hospital duration. However, early BAL in severe cases might not shorten the course of the disease or improve prognosis and may even increase the risks of mechanical ventilation and BAL complications.